LAND DEGRADATION DETECTION USING GEO-INFORMATIONTECHNOLOGY FOR SOME SITES IN IRAQ - Fadhil, Ayad Mohammed (Al-Nahrain Journal of Science, 2018)
This study aimed at monitoring, mapping, and assessing the land degradation in the upper Mesopotamian plain of Iraq. The country suffers severely due to land degradation and desertification problems, especially in its central and southern parts. Five vegetative, soil, and water indices related to land degradation were applied to two Landsat TM and ETM+ imageries to assess the extent of land degradation for the study area during the period from 1990 to 2000. A computerized land degradation severity assessment was adopted using ERMapper 7.1, Erdas Imagine 9.2, ArcView 3.3, and ArcGIS 9.1 environments to process, manage, and analysis the raster and thematic datasets. The indices used in this research are: The Normalized Difference Vegetation Index “NDVI”, The Normalized Differential Water Index “NDWI”, Tasseled Cap Transformation Wetness “TCW”, and a new index proposed in this study that is the Normalized Differential Sand Dune Index "NDSDI". The results showed a clear deterioration in vegetative cover (2620.4 km2), an increase of sand dune accumulations (1018.8 km2), and a decrease in soil/vegetation wetness (1720.4 km2), accounting for 12.9, 5.0, and 8.5 percent, respectively, of the total study area. In addition, a decrease in the water bodies area was detected (228.1 km2). Sand dunes accumulations had increased in the total study area, with an annual increasing expansion rateof (10.2 km2year-1) during the ten years covered by the study. The land degradation risk in the study area has increased by 111% during the study period. The statistical analysis of the results indicated that the soil/vegetation wetness is the biggest influence in the process of land degradation in the study area. The high performance of the NDSDI is promising and effective for identifying the sand dunes accumulations in the area of study. This study finds reveals that most of the counties in the study area are exposed to a serious risk of land degradation and drought water bodies.